Analisis Pengaruh Kepemimpinan Terhadap Kinerja Organisasi pada Periode 2022-2023: Studi Kasus - Luluk Tri Harinie; Puput Iswandyah Raysharie; Ade Saputra Sukma Wijaya; Ananda Halimah; Andrey Anggiat Imannuel Simanjuntak; Ella Afrida Purba; Krisna Krisna; Meisya Rasyiana; Nina Lestari; Rahmat Agus Prakoso; Rusmilla Rusmilla (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to evaluate the impact of certain leadership styles on the efficiency of student groups studying management, especially in HMJ management as an institution. The research respondents were students from class of 2022 majoring in Management, who were required to fill out a survey as part of this research. Using direct regression analysis, this study aims to identify whether a leader's views influence their organization's bottom line. The results of the study show that the views of leaders have a positive and significant influence on the performance of student organizations in management or HMJ management. This research makes an important contribution to leadership development in management student association organizations or HMJ management, especially in developing effective leadership attitudes. Therefore, organizational leaders need to pay attention to the needs and expectations of organizational members and obtain feedback from them to improve the quality of their leadership attitudes and overall organizational performance.